Analisis Penggunaan Aset dalam Pengukuran Profitabilitas PT Adaro Minerals Indonesia Tbk - Wahyul Huda Nanda; Sabariah Sabariah; Rona Lamretta Sinurat; Rina Br Bukit (Dinasti Research, 2023)
The primary objective of this study is to examine and assess the correlation between the utilisation of assets and the profitability of PT Adaro Minerals Indonesia Tbk, commonly referred to as AMI. The study employed a descriptive analytic methodology. Based on the data spanning from 2020 to 2022, it was observed that, with the exception of the working capital ratio in 2022, there was a consistent upward tendency in the account receivable turnover ratio, fixed asset turnover ratio, and total asset turnover ratio of the company. This pattern ultimately contributed to the overall stability of the company's profitability. The profitability ratios, including Gross Profit Margin (GPM), Net Profit Margin (NPM), Operating Margin, and Return on Assets (ROA) ratios, exhibit an upward trend for the period spanning from 2020 to 2022. The rise in the activity ratio can typically be attributed to a decline in firm assets, followed by an annual gain in income. The effective utilisation of assets inside a company exhibits a strong correlation with the company's profitability, which has demonstrated a consistent and upward trend over the past three years. The upward trajectory observed in the company's account receivable turnover, fixed asset turnover, total asset turnover, and cash turnover ratios has led to a corresponding enhancement in the company's profitability.